GAMBARAN ASUPAN NUTRISI DIMASA PANDEMI PADA MAHASISWA - Dewi, Novita; Maemunah, Neni; Putri, Ronasari Mahaji (Universitas Tribhuwana Tunggadewi, 2020)
Nutritional intake is needed by every human being to fulfill his survival. Proper nutrition results in the fulfillment of nutrients so that they can fight the COVID-19 virus. Covid-19 is at risk for students, most of whom are still dependent on their parents. The aim of the study was to describe the nutritional intake during the pandemic for students. This study uses an exploratory narrative method, with a cross-sectional approach. The instrument is a geogle form. Sampling by purposive sampling. The results showed that respondents in the second semester were 18 people (52.9%), respondents aged 20-22 years were 27 people (79%), respondents had an allowance of